2005
DOI: 10.1159/000082353
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Quality of Life in Late-Stage Dementia Scale to Psychotropic Drug Treatment in Late-Stage Dementia

Abstract: Background: We report on the responsiveness of a previously validated quality-of-life scale, the Quality of Life in Late-Stage Dementia scale (QUALID), as an outcome measure in a clinical trial of two psychotropic medications. Methods: Secondary analyses were conducted comparing outcome measures used in a randomized double-blind trial of two antipsychotics (olanzapine and risperidone) for the treatment of dementia-related behavioral symptoms. The QUALID was completed for 31 of the patients in addition to sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
1
31
0
3
Order By: Relevance
“…A study by Benhabib et al [20] found an association between QUALID and NPS assessed with NPI, but there was no significant association between change in QUALID and change in NPS. On the other hand, Martin-Cook et al [21] found that QUALID was responsive to changes in NPS assessed with NPI. Benhabib et al [20] interpreted their findings as a need for a more sensitive QoL assessment scale, but we assume that a more likely explanation is that QoL is a more stable phenomenon than NPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Benhabib et al [20] found an association between QUALID and NPS assessed with NPI, but there was no significant association between change in QUALID and change in NPS. On the other hand, Martin-Cook et al [21] found that QUALID was responsive to changes in NPS assessed with NPI. Benhabib et al [20] interpreted their findings as a need for a more sensitive QoL assessment scale, but we assume that a more likely explanation is that QoL is a more stable phenomenon than NPS.…”
Section: Discussionmentioning
confidence: 99%
“…We found 3 studies investigating the psychometric properties of QUALID: a study of the original QUALID [15], a study of the Swedish version of QUALID [16], and a study of the Spanish version of QUALID [17]. In addition, 2 Norwegian studies report a factor analysis of the Norwegian version of QUALID [12,18], 2 studies investigate variables associated with QUALID and with change in QoL [13,19] and 2 papers report results regarding QUALID's responsiveness to change [20,21]. This paper reports on the development of the Norwegian version of QUALID, and the results of a study on the psychometric properties of this version.…”
Section: Introductionmentioning
confidence: 99%
“…When first published, the internal consistency (Cronbach's alpha) of the scale was 0.769, and the inter-rater reliability (intraclass correlation) was 0.826. The QUALID scale consists of 11 items concerning both positive and negative dimensions of concrete and observable mood and performance, thought to be indicative of QoL in late-stage dementia [21]. The items are rated as to frequency of occurrence during the previous week on a five-point Likert-type scale.…”
Section: Instrumentsmentioning
confidence: 99%
“…Dit geldt zowel voor de dagelijkse praktijk als voor het meten van effecten van interventies in wetenschappelijk onderzoek. [1][2][3][4][5] Het bepalen van kwaliteit van leven bij dementie is geen eenvoudige opgave. Over zowel het concept 'kwaliteit van leven bij dementie', als het verkrijgen van valide en betrouwbare informatie is veel discussie.…”
Section: Inleidingunclassified
“…2 De Quality of Life in Late Stage Dementia schaal (QUALID) is een veelbelovende, in de Verenigde Staten ontwikkelde, eenvoudige vragenlijst van 11 items die speciaal ontworpen is om kwaliteit van leven bij gevorderde dementie te laten scoren door verzorgenden en helpenden ('licensed vocational nurses' en 'nurse aids'). 1,15 De QUALID wordt gebruikt in 5-jarig prospectief onderzoek naar levenseindezorg in Nederland en de VS. 16,17 In dit artikel richten wij ons op de vraag of de QUALID in de Nederlandse vertaling een valide en betrouwbaar instrument is om de kwaliteit van leven te meten bij gevorderde dementie. Voor beoordeling van de validiteit hebben wij, vanuit de benadering dat (psychisch) welbevinden een geschikte uitkomstmaat is voor kwaliteit van leven, 7 de QUALIDscores vergeleken met direct bij de patiënt geobserveerd onwelbevinden en er is een vergelijk gemaakt met een totaalindruk van het verzorgend personeel van de kwaliteit van leven van de patiënt.…”
Section: Inleidingunclassified